Strategi Pemasaran di Toserba Sunan Drajat Perspektif Ekonomi Syariah - Musthofa, R. Zainul; Aminah, Siti (Al-Muzdahir : Jurnal Ekonomi Syariah, 2023)
In every company must have a different marketing strategy, but there may also be the same. It's the same with the Sunan Drajat Department Store, because this is done in order to direct business efforts towards success. While we as Muslims in running a business, it is not enough just to implement strategies that are widely used by conventional people, but these strategies must also be based on sharia principles and values. The research method used is a qualitative research method, which is sourced from primary and secondary data, and uses data collection techniques including; observation, interview, and documentation. The results of this study are: 1. The marketing strategy implemented by the Sunan Drajat Department Store, includes: a. In terms of price, that is not only looking for profit but also for charity (as a supporter of PPSD development). b. In terms of location, namely always maintaining the cleanliness of the location. c. In terms of HR (people), namely trying to provide good service to consumers. d. Promotion is trying to be honest in introducing products to consumers. 2. In determining or assessing the strategy implemented by the Sunan Drajat Department Store with sharia principles, there are several indicators that must be met, including: a. The principle of Rabbaniyah, namely not only seeking worldly benefits, but also the hereafter. b. Ethical Principles, namely providing good service to consumers. c. Realistic Principles, that is clean, tidy, understated, flexible, and flexible in appearance. d. Humanistic Principles, namely providing universal services. In conclusion, it can be seen that the marketing strategy implemented by the department store is in accordance with sharia marketing principles.